Realist climate ethics: Promoting climate ambition within the Classical Realist tradition. Issue 1 (23rd July 2018) - Symons, Jonathan
Abstract: What is a Classical Realist analysis of climate ethics and politics? Classical Realist ethical analysis differs from ideal normative theory in that it addresses state decision-makers rather than individuals, assumes highly imperfect compliance with the demands of justice, and is concerned with feasibility and transition rather than end-states. Classical Realists urge leaders to prioritise state security over private moral concerns, to assess rival policies against their likely consequences and to seek the 'lesser evil' among feasible choices. But how does Realism respond when the prudent pursuit of state security risks rendering much of the planet uninhabitable? In the 1950s, the development of the hydrogen bomb created just such a dilemma as status quo politics now carried a significant risk of thermonuclear omnicide. In response, Hans Morgenthau argued that states should manage systemic risk by working in concert to safeguard expanded, collective national interests. The Classical Realist mode of thought suggests an analogous response to systemic climate risks: states' conceptions of national interest must expand to include cooperative system-preservation alongside traditional security concerns. Classical Realist arguments might then be mobilised to overcome resistance from vested interests and to support state-directed low carbon innovation, adaptation and mitigation agreements that prioritise ambition over distributional justice.